ANALISIS EFISIENSI USAHATANI PADI SAWAH DENGAN PENERAPANSISTEM TANAM JAJAR LEGOWO DI DESA ILOHELUMA KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - Hazra Abas; Amelia Murtisari; Yuriko Boekoesoe (Agrinesia: Jurnal Ilmiah Agribisnis, 2018)
This study aims to analyze: 1) Know the cost structure of farming on the application of planting system of row legowo paddy field in the village iloheluma Sub District Tilongkabila Bone Bolango District, 2) Analyze the efficiency of rice farming system with the application of legowo jajar planting system in Iloheluma Village Tilongkabila District Bone Bolango District from July to September of 2017. The method used is survey method that is data collection based on interview and observation. The sampling technique was done by using systematic sampling method. Namely sampling technique from a sequence of lists in a particular order where in this study the population consists of 160 people and taken from multiples of 5 so that get the sample of 33 people. Types and data sources used in this study are primary data and secondary data. Data analysis used is farming analysis by calculating total cost, acceptance, and R / C ratio and to analyze the efficiency of rice farming system using analysis of Cobb-Douglas Stochastic Frontier production function. The results showed that 1). the cost structure of paddy field farming in Iloheluma Village is a fixed cost of Rp.1,767,928 / ha or Rp.1.767.985 / ha and variable cost Rp.6.395.664 / farmer or equal to 7,745,207 / ha. 2). The average revenue received in the paddy field farming in Iloheluma Village is Rp. 7.335.590 / farmer or equal to 8,883,467 / ha. 3). For R / C ratio is the yield between total revenue (TR) divided by total cost (TC) is 1.93 advantageous. Wetland rice farming with the application of legowo jajar planting system has an effect on increasing production and efficiency of farming with seen from number of likehood estimation of production function model with MLE method that is equal to 0,625 bigger than amount of likehood estimation of production function model with OLS method that is equal to 0,580 where average efficiency of 0.70 or 70 percent. Factors - which affect the inefficiency of wet land farming ie age, education, experience of farming, joining farmer group, planting system and land status.